Rancang Bangun Sistem Informasi Layanan Pemesanan Furnitur Digital Berbasis Web untuk Meningkatkan Pengalaman dan Minat Beli Pelanggan - Poozasya Niagaralillah; Ahmad Fikri Salim; Rickar Aryel (Journal of Creative Student Research, 2026)
The development of information technology has significantly transformed business processes, including the furniture industry, which requires more efficient and flexible ordering systems. However, custom furniture ordering is still commonly conducted manually, resulting in inefficiencies, miscommunication, and limited access to information. This study aims to design and implement a web-based custom furniture ordering system that emphasizes simplicity, interactivity, and user experience. The research method used is Research and Development (R&D) with a qualitative approach through observation, interviews, and documentation. The system is developed using React technology to create a responsive interface and integrates WhatsApp as a communication medium between customers and business owners. The results show that the system successfully provides a digital catalog, structured product information, and a simplified ordering flow without complex forms. Functional evaluation indicates that users can easily understand the ordering process, access product information efficiently, and communicate directly with service providers. Overall, the system improves business process efficiency, expands marketing reach, and enhances customer experience in custom furniture services.